2013
DOI: 10.1213/ane.0b013e31828b3637
|View full text |Cite
|
Sign up to set email alerts
|

Carboetomidate

Abstract: Background Carboetomidate is a pyrrole etomidate analog that is 3 orders of magnitude less potent an inhibitor of in vitro cortisol synthesis than etomidate and does not inhibit in vivo steroid production. Although carboetomidate's reduced functional effect on steroid synthesis is thought to reflect lower binding affinity to 11β-hydroxylase, differential binding to this enzyme has never been experimentally demonstrated. In the current study, we tested the hypothesis that carboetomidate and etomidate bind with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…3336 In the CoMFA approach, there are no a priori assumptions regarding the nature of the protein binding site. Instead, the molecular (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3336 In the CoMFA approach, there are no a priori assumptions regarding the nature of the protein binding site. Instead, the molecular (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The safe dosage range of etomidate has been diminishing owing to its inhibition of adrenocortical function, as the suppression following even a single bolus may last 72 h ( Molenaar et al, 2012 ). This inhibition is mainly the result of the high-affinity binding between the basic nitrogen in the imidazole ring of etomidate and the heme iron on 11β-hydroxylase ( Den Brinker et al, 2008 ; Fellows et al, 1983 ; Shanmugasundararaj et al, 2013 ). In the 1980s, etomidate was used as a sedative for critically ill patients; however, in 1983, Watt and colleagues found that the continuous infusion of etomidate may increase mortality, and they speculated that the increased mortality is mainly caused by adrenocortical suppression.…”
Section: Discussionmentioning
confidence: 99%
“…12,33 This inhibition is remarkably potent, occurring even at nanomolar etomidate concentrations. 14,34,35 Computational docking studies using homology models of 11β-hydroxylase and spectroscopic studies using heterologously-expressed and purified enzyme indicate that etomidate’s high inhibitory potency arises primarily from its ability to engage in a coordination bond with the heme iron located within the enzyme’s active site. 14 This site is believed to be hydrophobic, a feature that would also enhance the binding of etomidate and other hydrophobic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…811 Etomidate is believed to suppress adrenocortical function primarily by binding within a heme-containing cavity that forms the active site of 11β-hydroxylase, thus inhibiting the enzyme’s function. 1214 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation